Pengaruh Current Ratio, Inventory Turnover dan Debt To Equity Ratio Terhadap Return On Asset pada PT Maha Agung - Abdul Khalik (Amsir Management Journal, 2021)
This research aims to find out the influence of current ratio, inventory turn over and debt to equity ratio on return on an asset in PT. Maha Agung Branch Parepare. The method of data analysis used in this study is financial ratio analysis and multiple linear analysis that aims to find out how much influence dependent variables have on independent data collection in research in the form of field research and literature research. The population and samples in this study report the sustainability of neraca and profit and loss. Partial calculation using the t hitung, that the coefficient of the t hitung result of the Current Ratio (CR) shows a significance level of 0.004 < 0.05. For thitung 15,082 > 4,303, indicates that the Current ratio affects return on asset. For the coefficient of t-Test results from Inventory, Turnover shows a significance level of 0.072 > 0.05. T calculated 3,516 < 4,303, showing Inventory Turnover does not affect Return on Asset. For the coefficient of t hitung results of the Debt to equity, Ratio shows a level of significance of 0.007 < 0.05. For t hitung 12,230 > 4,303, indicates debt to equity ratio affects return on asset. For silmultan test results use test value f to show the value sig. 0.009 > 0.05 then concluded simultaneously Current Ratio, Inventory Turnover, Debt to equity against Return on Asset.